Zirconium silicate fluorescent powder capable of being excited by purple light to emit red light as well as preparation method and application of zirconium silicate fluorescent powder
By introducing rare earth ions into zirconium silicate phosphor and using high-temperature solid phase method and other synthesis methods, red phosphor with excitation band located in the violet light area was prepared, which solved the problem that the excitation band of the existing phosphor does not match the violet light, and achieved efficient full-spectral illumination effect.
Patent Information
- Application Number
- CN202411635699.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The excitation band of the existing three-primary color phosphor cannot match the purple light area, and there are problems such as reabsorption and different degradation rates, which limit the development of full spectrum illumination.
Zirconium silicate phosphor is prepared by high-temperature solid phase method, sol-gel method, hydrothermal synthesis method and other methods. By introducing rare earth ions, the red fluorescence emission of the excitation band is located in the violet light region is achieved.
It achieves red emission of about 600 nm under purple light excitation of about 400 nm, with excellent physical and chemical stability and efficient luminous performance, and can be used to prepare white LEDs with high color rendering index.
Smart Images

Figure CN119529834A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fluorescent materials, and particularly relates to a zirconium silicate fluorescent powder which can be excited by purple light to emit red light, and a preparation method and application thereof. Background Art
[0002] White light LED (White Light Emitting Diode, WLED) as a new type of green environmentally friendly solid lighting source, known as the most valuable new light source in the 21st century, has broad application prospects in many fields. At present, the mainstream solution to achieve white light LED is to combine the chip with matching phosphor to produce white light, that is, fluorescent conversion white light LED. Usually, blue LED chip and YAG:Ce 3+ The yellow phosphor combination produces white light, but the white light obtained by this method lacks red light components, and the "blue enrichment" of the blue light chip may affect human physiological health. More research points to the use of purple LED chips to excite the three primary color phosphors to synthesize green healthy lighting with high luminous intensity and color rendering index.
[0003] However, the excitation bands of the existing three-primary color phosphors cannot achieve a good match with the purple region, and there are problems such as reabsorption and different degradation rates that limit the development of full-spectrum lighting. At the same time, some high-efficiency red phosphors are mostly fluorides and nitrides, such as SrLiAl 3 N 4 :Eu 2+ , K 2 SiF 6 :Mn 4+ However, its further application is subject to the disadvantages of harsh synthesis conditions and poor chemical stability, especially the mismatch with purple light chips. Therefore, it is particularly important to select a simple synthesis method and a suitable rare earth ion oxide matrix to synthesize red phosphors with an excitation band in the purple region. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a zirconium silicate phosphor that can be excited by purple light to emit red light, and a preparation method and application thereof, so as to overcome the technical defects that most of the phosphor excitation bands in the prior art are located in the blue light region, cannot be matched with purple light chips to achieve efficient white light emission, and the white light has a low color rendering index and lacks red light components, and cannot meet the needs of full-spectrum lighting.
[0005] The fluorescent material of the present invention can be excited by violet light of about 400nm, realizes red emission of about 600nm, has excellent luminescent performance, has outstanding physical and chemical stability, and can be used to prepare white light LEDs.
[0006] The present invention provides a fluorescent material, the fluorescent material compound has the general formula: X 2 YSn O 2n+3 :xM, wherein X is at least one of K, Na, and Rb; Y is at least one of Zr, Ti, and Hf; n≥1; x is 0 to 1; and M is one or more of the rare earth elements.
[0007] As the fluorescent material includes Na 2 YS0 5 :xM,Na 2 YS 2 O 7 :xM,X 2 ZrSiO 5 :xM,X 2 ZrSi 2 O 7 : one or more of xM, wherein X=one or more of K, Na, Rb; Y=one or more of Zr, Ti, Hf, x is 0-0.1; M is one or more of rare earth elements.
[0008] Preferably, the compound has the general formula Na 2 ZrSi n O 2n+3 :xM, wherein n≥1; x is 0-1; and M is one or more rare earth elements.
[0009] Further preferably, the general formula: Na 2 ZrSi n O 2n+3 (n=1,2):xM, wherein the value range of x is 0~0.4; M is one or more rare earth elements.
[0010] Preferably, n=1 or 2; x is 0-0.4; and the rare earth element is one or more of Sm, Eu, Dy, Cr, and Tb.
[0011] The present invention provides a method for preparing the fluorescent material, which comprises: preparing the fluorescent material by one or more of the following methods: high temperature solid phase method, sol-gel method, hydrothermal synthesis method, combustion method, chemical coprecipitation method, etc., using sodium silicate zirconium oxide as a matrix and rare earth ions as activating ions.
[0012] Preferably, the present invention provides a method for preparing a fluorescent material, comprising method 1 or method 2:
[0013] Method 1 comprises: using raw materials of a compound containing X, a compound containing Y, a compound containing Si, and a compound containing a rare earth element, according to the molecular formula X 2 YS n O 2n+3: The stoichiometric ratio of the corresponding elements in xM is weighed, mixed and fully ground to obtain a mixed powder, pre-fired, pressed into tablets, and then solid-phase reacted to obtain a fluorescent material;
[0014] Method 2 comprises: using raw materials of a compound containing X, a compound containing Y, a compound containing Si, and a compound containing a rare earth element, according to the molecular formula X 2 YS n O 2n+3 : weigh each raw material in the stoichiometric ratio of the corresponding elements in xM, then mix with nitric acid solution, perform hydrothermal reaction, and obtain a fluorescent material;
[0015] In the method 1 and the method 2, X is at least one of K, Na and Rb; Y is Zr, Ti and Hf; and M is one or more of the rare earth elements.
[0016] Preferably, in the method 1 and the method 2, the compound containing X is a carbonate of X; the compound containing Y is an oxide of Y; the compound containing Si is an oxide of Si; and the compound containing a rare earth element is an oxide of a rare earth element.
[0017] Furthermore, the raw material includes Na 2 CO 3 , ZrO 2 , SiO 2 , Sm 2 O 3 and Eu 2 O 3 .
[0018] Preferably, the grinding time in method 1 is 5 min to 10 h, and the mixture is mixed in agate mortar and ground thoroughly;
[0019] Preferably, the pre-calcination in the method 1 is performed at 800 to 900° C. for 1 to 3 hours;
[0020] Preferably, the solid phase reaction in the method 1 is carried out at 1100-1300° C. for 4-8 hours.
[0021] Preferably, in the method 1, the heating rate during pre-calcination is 1.5 to 20° C. / min; and the heating rate during the solid phase reaction is 1.5 to 20° C. / min.
[0022] Preferably, in the method 1, the tabletting pressure is 5 to 30 MPa, and the tablet diameter is 5 to 15 mm.
[0023] Furthermore, in the method 1, the pre-sintered product is ground again and then tableted.
[0024] After the solid phase reaction in the method 1 is completed, the mixture is cooled to room temperature and ground.
[0025] In the method 1, the mixed powder is fully ground to obtain a mixed powder, which is then transferred to a crucible (such as an alumina crucible), pre-fired in a muffle furnace, and the pre-fired powder is pressed into tablets, placed in a high-temperature muffle furnace for high-temperature solid-phase reaction, taken out after cooling, and ground again to obtain a phosphor.
[0026] Preferably, the hydrothermal reaction in method 2 is carried out at 80 to 120° C. for 6 to 24 hours;
[0027] Preferably, after the hydrothermal reaction in method 2 is completed, the product is filtered, washed, and vacuum dried for 12 to 36 hours.
[0028] In the method 2, after being mixed with a nitric acid solution and subjected to magnetic stirring, the mixture is sealed in a stainless steel autoclave for hydrothermal reaction, the autoclave is naturally cooled to room temperature, the obtained white solid product is filtered, washed with distilled water, and vacuum dried at room temperature for 12 to 36 hours to obtain a phosphor powder.
[0029] The red phosphor prepared according to the above process is measured under different excitation light bands to detect its luminescence characteristics.
[0030] The present invention provides an application of the fluorescent material in the field of lighting, such as application in the field of LED in combination with a purple light chip to achieve green full-spectrum lighting.
[0031] The fluorescent material of the present invention can be effectively excited by 400nm violet light to achieve red light emission of 600-617nm, and can be assembled into a white light LED with commercial fluorescent powder to achieve green full-spectrum lighting.
[0032] The present invention provides a zirconium silicate red phosphor that can be effectively excited by the violet light band, which can effectively improve the color rendering index when preparing white light LEDs and realize full-spectrum lighting. The phosphor prepared by the present invention has strong red luminescence, excellent thermal stability and high temperature and high humidity resistance. The excitation band is located in the violet light region, and can be matched with a violet light chip to achieve full-spectrum lighting, meeting the needs of green and healthy lighting. The present invention provides a method for preparing phosphors by two-step pre-firing in a high-temperature solid phase method. The present invention introduces rare earth ions into a zirconium silicate matrix to achieve red light emission.
[0033] Beneficial Effects
[0034] (1) The red phosphor obtained by the present invention not only meets the basic requirements of "excitation by purple light and realization of narrow-band red emission", but also has the characteristics of excellent resistance to high temperature and high temperature and humidity.
[0035] (2) Compared with traditional red phosphors, the excitation band of the phosphors of the present invention is accurately located in the purple light region and can be used with purple light chips to achieve high-efficiency green full-spectrum white light lighting needs.
[0036] (3) The red phosphor of the present invention has excellent resistance to high temperature and high humidity. The LED prepared and assembled with the commercial powder has a high color rendering index of 89, which effectively realizes full-spectrum lighting and has great application prospects in the direction of green lighting. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the XRD spectrum of the phosphors prepared by the high temperature solid phase method in Example 1(a) and Example 2(b);
[0038] Figure 2 is the excitation and fluorescence spectra of the phosphor prepared in Example 4;
[0039] Figure 3 The following are the CIE diagram (a) and luminescence spectrum diagram (b) of the LED device assembled with the phosphor prepared in Example 5.
[0040] Figure 4 (a~d) are characterization diagrams of the high temperature resistance performance of the phosphor prepared in Example 6.
[0041] Figure 5 (a~b) are characterization diagrams of the high temperature and high humidity resistance of the phosphor prepared in Example 6. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0043] Table 1 Source of raw materials
[0044] raw material Specification Manufacturer <![CDATA[Sodium carbonate (Na 2 CO 3 )]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. <![CDATA[Zirconia (ZrO 2 )]]> Analytical grade BID Pharmaceutical Group Co., Ltd. <![CDATA[Silicon dioxide (SiO 2 )]]> Analytical grade Alcon <![CDATA[Samarium(III) oxide 2 O 3 )]]> Analytical grade Alcon <![CDATA[Europium oxide (Eu 2 O 3 )]]> Analytical grade Alcon
[0045] Table 2 Test methods and standards
[0046]
[0047] Example 1
[0048] Sodium carbonate (1.0590g), zirconium dioxide (1.2322g), silicon dioxide (0.5999g), samarium oxide (0.0523g) and europium oxide (0.0879g) were weighed in a standard analytical balance according to the stoichiometric ratio, and the raw materials were mixed into an agate mortar according to the ratio, and they were fully ground for 15 minutes until all the raw materials were fully mixed. The mixed powder was spread in an alumina crucible, placed in a muffle furnace and pre-fired at 850°C for 3h. After the pre-burning was completed, the powder was taken out and ground again, and the powder was pressed into 10mm discs at a pressure of 10MPa using a manual tablet press. The disc was placed in an alumina crucible again, placed in a high-temperature muffle furnace and reacted at 1180°C for 4h. The disc after the secondary reaction was taken out and cooled, and ground again to successfully synthesize Na 2 ZrSiO 5 :Sm 3+ / Eu 3+ Red phosphor.
[0049] To Na 2 ZrSiO 5 The XRD phase characterization of the intrinsic and Sm and Eu rare earth element doped red phosphors was performed, and the results were as follows Figure 1 a: The diffraction peaks and Na 2 ZrSiO 5 phase (PDF#72-1863J), further proving that rare earth elements were successfully doped into Na 2 ZrSiO 5 in the matrix.
[0050] Example 2
[0051] Sodium carbonate (1.0590g), zirconium dioxide (1.2322g), silicon dioxide (1.1999g), samarium oxide (0.1221g) and europium oxide (0.2114g) were weighed in a standard analytical balance according to the stoichiometric ratio, and the raw materials were mixed into an agate mortar according to the ratio, and they were fully ground for 15 minutes until all the raw materials were fully mixed. The mixed powder was spread in an alumina crucible, placed in a muffle furnace and pre-fired at 850°C for 3h. After the pre-burning was completed, the powder was taken out and ground again, and the powder was pressed into 10mm discs at a pressure of 10MPa using a manual tablet press. The disc was placed in an alumina crucible again, placed in a high-temperature muffle furnace and reacted at 1300°C for 8h. The disc after the secondary reaction was taken out and cooled, and ground again to successfully synthesize Na 2 ZrSi 2 O 7 :Sm 3+ / Eu 3+ Red phosphor.
[0052] To Na2 ZrSi 2 O 7 The XRD phase characterization of the intrinsic and Sm and Eu rare earth element doped red phosphors was performed, and the results were as follows Figure 1 b: The diffraction peaks and Na 2 ZrSi 2 O 7 The peak shape of the phase (JCPDS#29-1293) is consistent, which further proves that rare earth elements are successfully doped into Na 2 ZrSi 2 O 7 in the matrix.
[0053] Example 3
[0054] Sodium carbonate (1.0590 g), zirconium dioxide (1.2322 g), silicon dioxide (0.5999 g), samarium oxide (0.0523 g) and europium oxide (0.0879 g) were weighed in a standard analytical balance according to the stoichiometric ratio, mixed with nitric acid solution, magnetically stirred, sealed in a stainless steel autoclave, and kept at 100 ° C for 12 h. After the reaction, the autoclave was naturally cooled to room temperature. The obtained white solid product was filtered, washed with distilled water, and vacuum dried at room temperature for 24 h to obtain Na 2 ZrSiO 5 :0.03Sm 3+ and Na 2 ZrSiO 5 :0.05Eu 3+ Red phosphor powder.
[0055] Similarly, sodium carbonate (1.0590 g), zirconium dioxide (1.2322 g), silicon dioxide (1.1999 g), samarium oxide (0.1221 g) and europium oxide (0.2114 g) were weighed in a standard analytical balance according to the stoichiometric ratio, mixed with nitric acid solution, magnetically stirred, sealed in a stainless steel autoclave, and kept at 100 ° C for 12 h. After the reaction, the autoclave was naturally cooled to room temperature. The obtained white solid product was filtered, washed with distilled water, and vacuum dried at room temperature for 24 h to obtain Na 2 ZrSi 2 O 7 :0.07Sm 3+ and Na 2 ZrSi 2 O 7 :0.12Eu 3+ Red phosphor powder.
[0056] Example 4
[0057] The first group of sodium carbonate (1.0590 g), zirconium dioxide (1.2322 g), silicon dioxide (0.5999 g), samarium oxide (0.0523 g) were weighed on a standard analytical balance according to the stoichiometric ratio; the second group of sodium carbonate (1.0590 g), zirconium dioxide (1.2322 g), silicon dioxide (0.5999 g), europium oxide (0.0879 g) were weighed; the third group of sodium carbonate (1 .0590g), zirconium dioxide (1.2322g), silicon dioxide (1.1999g), samarium oxide (0.1221g); the fourth group of sodium carbonate (1.0590g), zirconium dioxide (1.2322g), silicon dioxide (1.1999g), europium oxide (0.2114g) are mixed into an agate mortar according to the ratio, and fully ground for 15 minutes until all the raw materials are fully mixed. The mixed powder is spread in an alumina crucible and placed in a muffle furnace for reaction and pre-burning at 850℃ for 3h. After the pre-burning is completed, the powder is taken out and ground again, and the powder is pressed into a 10mm disc at a pressure of 10MPa using a manual tablet press. The disc is placed in an alumina crucible again and placed in a high-temperature muffle furnace for reaction at 1180℃ for 4h in the first and second groups, and at 1300℃ for 8h in the third and fourth groups. The wafer after the secondary reaction was taken out, cooled, and ground again to successfully synthesize Na 2 ZrSiO 5 :0.03Sm 3+ 、Na 2 ZrSiO 5 :0.05Eu 3+ 、Na 2 ZrSi 2 O 7 :0.07Sm 3+ and Na 2 ZrSi 2 O 7 :0.12Eu 3+ Red phosphor.
[0058] The prepared phosphor was tested for excitation and emission spectra, and the results were as follows: Figure 2 The excitation band of the silicate red phosphor is located in the violet region of 343-405 nm, and the narrow-band red emission peak is located at about 600-617 nm.
[0059] Example 5
[0060] In this embodiment, Na 2 ZrSi 2 O 7 :0.07Sm 3+ Red phosphor with commercial phosphor BaMgAl 10 O 17 :Eu 2+(BAM),Lu 3 Al 5 O 12 :Ce(LuAG) was used to prepare white light LED. First, the red, green and blue primary color phosphors were mixed and fully ground for 15 minutes. The mixed phosphor powder was mixed with AB glue at a powder-to-glue ratio of 1:10 and then placed in a vacuum oven for 1 hour to remove the optical bonding bubbles in the reagent. The mixture was then evenly coated on a 410nm LED chip and cured at 150°C to obtain an LED device. The color temperature (CCT) and luminous efficiency of the fabricated WLED were measured using an LED optoelectronic integrated detection system (HP9000, Hopoo, China).
[0061] The results are as follows Figure 3 As shown, Na 2 ZrSi 2 O 7 :0.07Sm 3+ The white light LED prepared by combining the phosphor with commercial phosphor BAM, LuAG and 410nm purple light chip has a high color saturation Rg = 104 and an excellent color rendering index Ra = 89.6. It is proved that the zirconium silicate phosphor of the present invention can be effectively excited by purple light to achieve red emission, make up for the red band of the full spectrum, improve the color rendering index, and has great prospects in the field of full-spectrum green lighting.
[0062] Example 6
[0063] The first group of sodium carbonate (1.0590 g), zirconium dioxide (1.2322 g), silicon dioxide (0.5999 g), samarium oxide (0.0523 g) were weighed on a standard analytical balance according to the stoichiometric ratio; the second group of sodium carbonate (1.0590 g), zirconium dioxide (1.2322 g), silicon dioxide (0.5999 g), europium oxide (0.0879 g) were weighed; the third group of sodium carbonate (1 .0590g), zirconium dioxide (1.2322g), silicon dioxide (1.1999g), samarium oxide (0.1221g); the fourth group of sodium carbonate (1.0590g), zirconium dioxide (1.2322g), silicon dioxide (1.1999g), europium oxide (0.2114g) are mixed into an agate mortar according to the ratio, and fully ground for 15 minutes until all the raw materials are fully mixed. The mixed powder is spread in an alumina crucible and placed in a muffle furnace for reaction and pre-burning at 850℃ for 3h. After the pre-burning is completed, the powder is taken out and ground again, and the powder is pressed into a 10mm disc at a pressure of 10MPa using a manual tablet press. The disc is placed in an alumina crucible again and placed in a high-temperature muffle furnace for reaction at 1180℃ for 4h in the first and second groups, and at 1300℃ for 8h in the third and fourth groups. The wafer after the secondary reaction was taken out, cooled, and ground again to successfully synthesize Na2 ZrSiO 5 :0.03Sm 3+ 、Na 2 ZrSiO 5 :0.05Eu 3+ 、Na 2 ZrSi 2 O 7 :0.07Sm 3+ and Na 2 ZrSi 2 O 7 :0.12Eu 3+ Red phosphor.
[0064] The prepared phosphor was tested for its high temperature resistance and high temperature and high humidity resistance. The results are as follows: Figure 4 and Figure 5 The silicate red phosphor has excellent anti-fluorescence thermal quenching performance. At 175℃, Na 2 ZrSiO 5 :0.03Sm 3+ The luminous intensity of the phosphor can still maintain 76% of that at room temperature. 2 ZrSi 2 O 7 :0.12Eu 3+ The luminous intensity of the phosphor can still maintain 78% of that at room temperature. 2 ZrSiO 5 :0.03Sm 3+ 、Na 2 ZrSiO 5 :0.05Eu 3+ 、Na 2 ZrSi 2 O 7 :0.07Sm 3+ and Na 2 ZrSi 2 O 7 :0.12Eu 3+ Four groups of phosphors were placed in a high humidity and heat environment (85°C, 85% RH) for accelerated aging experiments. The results showed that after being placed in a high humidity and heat environment for 24 hours, the phosphors could maintain more than 75% of their initial fluorescence intensity.
Claims
1. A fluorescent material, characterized in that: The fluorescent material compound has the general formula: X2YSi n O 2n+3 :xM, wherein X is at least one of K, Na, and Rb; Y is at least one of Zr, Ti, and Hf; n≥1; x is 0 to 1; and M is one or more of the rare earth elements.
2. The fluorescent material according to claim 1, characterized in that: The compound has the general formula of Na2ZrSi n O 2n+3 :xM, wherein n≥1; x is 0-1; and M is one or more rare earth elements.
3. The fluorescent material according to claim 1, characterized in that: The n=1 or 2; the x is 0-0.4; the rare earth element is one or more of Sm, Eu, Dy, Cr, and Tb.
4. A method for preparing the fluorescent material according to any one of claims 1 to 3, characterized in that: The preparation method includes one or more of a high temperature solid phase method, a sol-gel method, a hydrothermal synthesis method, a combustion method, and a chemical co-precipitation method.
5. A method for preparing a fluorescent material, comprising method 1 or method 2: Method 1 includes: The raw materials are compounds containing X, Y, Si, and rare earth elements, according to the molecular formula X2YSi n O 2n+3 : The stoichiometric ratio of the corresponding elements in xM is obtained by weighing the raw materials, grinding, pre-burning, pressing, and then solid phase reaction to obtain the fluorescent material; Method 2 comprises: using raw materials of a compound containing X, a compound containing Y, a compound containing Si, and a compound containing a rare earth element, according to the molecular formula X2YSi n O 2n+3 : weigh each raw material in the stoichiometric ratio of the corresponding elements in xM, then mix with nitric acid solution, perform hydrothermal reaction, and obtain a fluorescent material; In the method 1 and the method 2, X is at least one of K, Na and Rb; Y is Zr, Ti and Hf; and M is one or more of the rare earth elements.
6. The preparation method according to claim 5, characterized in that: In the method 1 and the method 2, the compound containing X is a carbonate of X; the compound containing Y is an oxide of Y; the compound containing Si is an oxide of Si; and the compound containing a rare earth element is an oxide of a rare earth element.
7. The preparation method according to claim 5, characterized in that: The grinding time in method 1 is 5 min to 10 h; In the method 1, the pre-calcination is performed at 800 to 900° C. for 1 to 3 hours; In the method 1, the solid phase reaction is carried out at 1100-1300° C. for 4-8 hours.
8. The preparation method according to claim 5, characterized in that: The heating rate during pre-calcination in the method 1 is 1.5 to 20°C / min; the heating rate of the solid phase reaction is 1.5 to 20°C / min; In the method 1, the tablet pressing pressure is 5-30 MPa, and the tablet diameter is 5-15 mm; grinding is performed after the solid phase reaction is completed.
9. The preparation method according to claim 5, characterized in that: In the method 2, the hydrothermal reaction is carried out at 80 to 120° C. for 6 to 24 hours; After the hydrothermal reaction in method 2 is completed, the mixture is filtered, washed, and vacuum dried for 12 to 36 hours.
10. Use of the fluorescent material according to any one of claims 1 to 3 in the field of lighting.
Citation Information
Patent Citations
Zirconium silicate salt blue fluorescent powder, preparation method and application thereof
CN104073255A
Cited By
Fluorescent powder as well as preparation method and application thereof
CN122037930A